Teaching Professional Identity, Reflection and Pedagogical Practice: Key Considerations for Teacher Training - Vanegas-Ortega, C (EDICIONES UNIV VALPARAISO, 2019)
The development of professional identity, reflection and pedagogical practice have become three key axes for the initial and ongoing teacher training. This article explains why reflexive processes allow situations to be resolved that stress the professional identity of teachers; it is constructed and transformed during pedagogical practices from three dynamically related axes: identification, identization and identity with the role of practice (as a teacher in training, tutor or guide).